Exploring Pre-service Science Teachers’ Knowledge and Understanding of the Nature of Science - Kadiyala, Aparna (JOURNAL OF INDIAN EDUCATION, 2016)
The present research is to explore pre-service science teachers’ knowledge and understanding of the nature of science by survey method using questionnaire and interview. The sample of the study included 693 pre-service science teachers under the Acharya Nagarjuna University by using random sample with disproportionate stratified sampling. Five per cent of the participating pre-service science teachers were interviewed following their responses in the questionnaire. In order to test the hypothesis, based on pre-service teachers’ knowledge and understanding levels, one sample t-test is used and results indicate lack of significant currently accepted knowledge and understanding of the nature of science. The study reveals patterns showing that the pre-service science teachers had inadequate and conflicting views on several aspects of the nature of science. The study mainly recommends explicit teaching of the nature of science, including aspects of history, philosophy and sociology of science.